Comparison of first-generation EGFR-TKIs combined with low-dose bevacizumab versus osimertinib in untreated advanced EGFR-mutated NSCLC - Yingqi Xu; Yidan Zhang; Hongping Jin; Hua Zhong; Jianlin Xu; Yuqing Lou; Runbo Zhong (Annals of Medicine)
Background This study aimed to compare the efficacy of first-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) combined with low-dose bevacizumab(7.5 mg/kg) versus osimertinib as first-line treatment in patients with advanced EGFR-mutated non-small cell lung cancer (NSCLC).Materials and methods A total of 161 patients with advanced NSCLC harboring EGFR mutations, who received first-line treatment at Shanghai Chest Hospital between July 2017 and July 2023, were enrolled in this study. Among them, 78 patients were treated with a combination of first-generation EGFR-TKIs and bevacizumab (7.5 mg/kg), constituting the bevacizumab plus TKI (A + T) group. The remaining 83 patients received osimertinib monotherapy (80 mg daily), forming the osimertinib group.Results The objective response rate (ORR) was 65.4% (51/78) in the A + T group and 68.7% (57/83) in the osimertinib group (p = 0.657). Despite the potentially poorer baseline conditions of patients in the osimertinib group, the median progression-free survival (PFS) was 16.59 months (95% CI: 14.39–18.80) in the A + T group compared to 16.82 months (95% CI: 13.76–19.89) in the osimertinib group (p = 0.792). Preliminary overall survival (OS) analysis indicated a median OS of 51.75 months (95% CI: 41.63–61.86) in the A + T group versus 35.55 months (95% CI: 22.32–48.77) in the osimertinib group (p = 0.010), however, the OS data are not yet mature.Conclusion Although osimertinib remains the preferred first-line treatment for advanced NSCLC with EGFR mutations, combining first-generation EGFR-TKIs with low-dose bevacizumab may be a viable alternative for certain patients.